Features of Database Types - Deineko, Zh.; Sotnik, S.; Vovk, O.; Lyashenko, V. (IJEAIS, 2021)
Research in field of developing databases and working with modern applications, their implementation in modern enterprises is constantly expanding, so issue of researching database features still requires further attention. This paper discusses functions that typical database management system (DBMS) should provide. The review is devoted to highlighting advantages and disadvantages of existing databases. The article summarizes material on key aspects that should be present in modern DBMS, which will allow you to better understand procedures for building, working and using them.
Keywords: database; architecture